The V617I Substitution in Avian Coronavirus IBV Spike Protein Plays a Crucial Role in Adaptation to Primary Chicken Kidney Cells - Jiang, Yi; Gao, Mingyan; Cheng, Xu; Yu, Yan; Shen, Xinyue; Li, Jianmei; Zhou, Sheng (Frontiers in Microbiology, 2020)
The naturally isolated avian coronavirus infectious bronchitis virus (IBV) generally cannot replicate in chicken kidney (CK) cells. To explore the molecular mechanism of IBV adapting to CK cells, a series of recombinant viruses were constructed by chimerizing the S genes of CK cell-adapted strain H120 and non-adapted strain IBYZ. The results showed that the S2 subunit determines the difference in cell tropism of the two strains. After comparing the amino acid sequences of S protein of CK cell-adapted strain YZ120, with its parental strain IBYZ, three amino acid substitutions, A138V, L581F, and V617I, were identified. Using YZ120 as the backbone, one or more of the above-mentioned substitutions were eliminated to verify the correlation between these sites and CK cell tropism. The results showed that the CK cell tropism of the YZ120 strain depends on the V617I substitution, the change of L581F promoted the adaptation in CK cells, and the change at 138 position was not directly related to the CK cell tropism. Further validation experiments also showed that V617I had a decisive role in the adaptation of IBV to CK cells, but other areas of the virus genome also affected the replication efficiency of the virus in CK cells.